The Influence of Emotional Intelligence, Work-Life Balance and Leadership Style on Generation Z Employee Loyalty on PT View Indonesia - Septiana Arvina; Nur Wening (Inkubis : Jurnal Ekonomi dan Bisnis, 2026)
Background: This research is motivated by the low level of loyalty among Generation Z employees, characterized by a high rate of job turnover and decreased organizational commitment. This condition is also observed in PT View Indonesia, which is dominated by Generation Z employees. Objective: This study aims to empirically examine the influence of emotional intelligence, work-life balance, and leadership style on the loyalty of Generation Z employees at PT View Indonesia, as well as to identify the individual contribution of each variable to employee loyalty outcomes. Method: The research employed a quantitative approach with data collected through questionnaires administered to 113 respondents using the saturated sampling method. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) through two stages: measurement model testing and structural model evaluation. Results: The findings indicate that emotional intelligence, work-life balance, and leadership style each have a positive and significant influence on the loyalty of Generation Z employees. Conclusion: The study concludes that these three variables are critical factors in enhancing the loyalty of Generation Z employees within the company.